Magnetoreception in multicellular magnetotactic prokaryotes: a new analysis of escape motility trajectories in different magnetic fields - Sepulchro, Ana Gabriela Veiga; de Barros, Henrique Lins; de Mota, Henrique Oliveira Leiras; Berbereia, Karen Shiroiva; Huamani, Katterine Patricia Taipe; Lopes, Lis Carneiro da Silva; Sudbrack, Vitor [UNESP]; Acosta-Avalos, Daniel (Springer Nature, 2020)
Magnetotactic microorganisms can be found as unicellular prokaryotes, as cocci, vibrions, spirilla and rods, and as multicellular organisms. Multicellular magnetotactic prokaryotes are magnetotactic microorganisms composed by several magnetotactic bacteria organized almost in a spherical helix, and one of the most studied is Candidatus Magnetoglobus multicellularis. Several studies have shown that Ca. M. multicellularis displays forms of behavior not well explained by magnetotaxis. One of these is escape motility, also known as “ping-pong” motion. Studies done in the past associated the “ping-pong” motion to some magnetoreceptive behavior, but those studies were never replicated. In the present manuscript a characterization of escape motility trajectories of Ca. M. multicellularis was done for several magnetic fields, considering that this microorganism swims in cylindrical helical trajectories. It was observed that the escape motility can be separated into three phases: (I) when the microorganism jumps from the drop border, (II) where the microorganism moves almost perpendicular to the magnetic field and (III) when the microorganism returns to the drop border. The total time of the whole escape motility, the time spent in phase II and the displacement distance in phase I decreases when the magnetic field increases. Our results show that the escape motility has several characteristics that depend on the magnetic field and cannot be understood by magnetotaxis, with a magnetoreceptive mechanism being the best explanation.
Keywords: Escape motility; Magnetoreception; Magnetotaxis; Multicellular magnetotactic prokaryote